Limiting Taxpayer "Puts" : An Example from Central Counterparties - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2014)
Nonbanks such as central counterparties (CCPs) are a useful lens to see how regulators view the role of the lender-of-last-resort (LOLR). This paper explores the avenues available when a nonbank failure is likely, specifically by considering the options of keeping CCPs afloat. It is argued that CCPs have, by regulatory fiat, become 'too important to fail,' and thus the imperative should be greater loss-sharing by all participants that better align the distribution of risks and rewards of CCPs, the clearing members and derivative end-users. In the context of LOLR, the proposed variation margin gains haircut (VMGH) is discussed as a way of limiting the taxpayer put.